Selection of two triticale varieties for forage-end use in Tunisia - Ben Youssef S.; Abidi S.; Jlidi R. (New approaches for grassland research in a context of climate and socio-economic changes, 2012)
Two new released triticale varieties (one spring type Tcl821 and one winter type, G41) were evaluated for their dry matter yield and nutritive value at three harvesting stages (first node detectable, Z31, late boot, Z50 and soft dough stag, Z85). Both genotypes confirmed their high dry matter yield potential at all stages. The winter triticale was more productive than the spring genotype at all growing stages. G41 presented a prostrate growth habit from emergence to first node detectable stage (Z31) and took much more time to reach that stage. Among the two cultivars, it was the best to be used by grazing or in dual-purpose system at early vegetative growth. At late boot stage (Z50), the winter type produced 9 T DM ha-1 of a high quality forage (CP = 15%; ADL = 3.8%, dOM = 60%). The spring triticale Tcl821 produced an equivalent forage quality but with half the yield potential (5 T DM ha-1). At soft dough stage, the spring triticale Tcl821 was as much productive as the winter genotype G41, but it produced a forage with much higher quality as expressed in terms of CP, ME and fibers. The agronomical meanings of the three key harvesting stages were discussed.
14. Meeting of the FAO-CIHEAM Subnetwork on Mediterranean Forages and Fodder Crops, 2012/10/03-06, Samsun (Turkey)